Re-implantation of suboptimal prostate seed implantation: technique with intraoperative treatment planning - Doyle, Laura (Termedia Publishing House, 2012)
PURPOSE: Post-implant dosimetry following prostate seed implantation (PSI) occasionally reveals suboptimal dosimetric coverage of the gland. Published reports of re-implantation techniques have focused on earlier-generation techniques, including preplanned approaches and stranded seeds. The purpose of this case report is to describe a customizable approach to perform corrective re-implantation using loose seeds and intraoperative planning technique. MATERIAL AND METHODS: This case report describes a 63-year-old male with favorable risk prostate adenocarcinoma receiving PSI. Thirty day post-implant dosimetric evaluation revealed suboptimal coverage of the base of the gland. Using guidance from post-implant CT-images and real-time planning, the patient received a corrective re-implantation with intraoperative planning. RESULTS: Post-implant dosimetry after re-implantation procedure with intraoperative planning yielded improved target volume coverage that achieved standard dosimetric criteria. CONCLUSIONS: Re-implantation as a salvage treatment technique after sub-optimal PSI is a valid treatment option performed with intraoperative real-time planning.